2021
DOI: 10.1007/s00402-021-04024-6
|View full text |Cite
|
Sign up to set email alerts
|

Results after primary reverse shoulder arthroplasty with and without subscapularis repair: a prospective-randomized trial

Abstract: Introduction Indications for reverse shoulder arthroplasties (rTSA) have increased since their development by Paul Grammont in 1985. Prosthesis design was enhanced over time, but the management of the tendon of the M. subscapularis (SSC-tendon) in primary rTSA is still a controversial subject with regard to perform a refixation or not. Methods 50 patients were randomized in a refixation group (A) and a non-refixation-group (B) of the SSC-tendon in a double… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 45 publications
1
10
0
Order By: Relevance
“…These studies support our findings that the sum of bipolar lateralization (more rotational movement (humeral lateralization [ 49 ]) and less notching (glenoidal lateralization) [ 30 , 52 ]) and distalization ( more flexion [ 50 ]) with inferior glenosphere overhang ( less notching [ 53 ]) provides best ROM despite no clinically significant difference in outcome scores could be found [ 30 , 46 , 52 , 54 ].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…These studies support our findings that the sum of bipolar lateralization (more rotational movement (humeral lateralization [ 49 ]) and less notching (glenoidal lateralization) [ 30 , 52 ]) and distalization ( more flexion [ 50 ]) with inferior glenosphere overhang ( less notching [ 53 ]) provides best ROM despite no clinically significant difference in outcome scores could be found [ 30 , 46 , 52 , 54 ].…”
Section: Discussionsupporting
confidence: 84%
“…The same 135° design as that used in our study showed better external rotation and greater abduction strength compared to a 155° design with a tGLO of 18.5 mm at the 1-year follow-up examination [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the only randomized trial on the topic, Engel et al studied 50 rTSA patients that were randomized to subscapularis repair vs. non-repair groups and found that repairing the subscapularis resulted in an improved Constant Score and internal rotation 12 months postoperatively. 10 The study however acknowledged a limitation of low sample size of 20 and 21 patients with follow-up in each group and a switch in prosthesis use part way through the study.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical significance of subscapularis repair is controversial in RSA. A prospective randomized trial by Engel et al [ 29 ] concluded that subscapularis tendon repair in RSA improves the Constant score and internal rotation at 12 months after surgery. In medialized design RSA, the subscapularis has an important role in preventing dislocation [ 30 ].…”
Section: Rotator Cuff Tearmentioning
confidence: 99%